Heat shock factor HSFA2 fine-tunes resetting of thermomemory via plastidic metalloprotease FtsH6. (15th June 2022) - Sedaghatmehr, Mastoureh; Stüwe, Benno; Mueller-Roeber, Bernd; Balazadeh, Salma
Abstract : The transcription factor HSFA2 fine-tunes a balance between prolongation and resetting of thermomemory in Arabidopsis via the regulation of both memory-supporting and memory-resetting genes. Abstract: Plants 'memorize' stressful events and protect themselves from future, often more severe, stresses. To maximize growth after stress, plants 'reset' or 'forget' memories of stressful situations, which requires an intricate balance between stress memory formation and the degree of forgetfulness. HEAT SHOCK PROTEIN 21 ( HSP21 ) encodes a small heat shock protein in plastids of Arabidopsis thaliana . HSP21 functions as a key component of thermomemory, which requires a sustained elevated level of HSP21 during recovery from heat stress. A heat-induced metalloprotease, filamentation temperature-sensitive H6 (FtsH6), degrades HSP21 to its pre-stress abundance, thereby resetting memory during the recovery phase. The transcription factor heat shock factor A2 (HSFA2) activates downstream genes essential for mounting thermomemory, acting as a positive regulator in the process. Here, using a yeast one-hybrid screen, we identify HSFA2 as an upstream transactivator of the resetting element FtsH6. Constitutive and inducible overexpression of HSFA2 increases expression of FtsH6, whereas it is drastically reduced in the hsfa2 knockout mutant. Chromatin immunoprecipitation reveals in planta binding of HSFA2 to the FtsH6 promoter. Importantly, overexpression of HSFA2 improves thermomemory more profoundly in ftsh6 than wild-type plants. Thus, by activating both memory-supporting and memory-resetting genes, HSFA2 acts as a cellular homeostasis factor during thermomemory.